2018
DOI: 10.1021/acs.jpcc.7b11060
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Salt Association and the Dielectric Properties of Low Permittivity Electrolytes: The Case of LiPF6 and LiAsF6 in Dimethyl Carbonate

Abstract: In this article, we present evidence that the dielectric constant of an electrolyte solution can be effectively used to infer the association regime of the salt species from computational methods. As case studies, we consider the low dielectric constant solvent dimethyl carbonate with LiAsF6 and LiPF6 salts at low concentrations. Using both quantum “ab initio” methods as well classical molecular dynamics simulations, we elucidate the salt’s contribution to the dielectric constant as well as the dipolar relaxat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 33 publications
1
49
0
Order By: Relevance
“…Molecular dynamics (MD) simulations were carried out with the GROMACS software, 26 and initial configurations were prepared using Packmol. 27 Forcefield parameters for THF were taken from Spoel et al, 28 Ca 2+ parameters from the standard OPLS library, and BH4parameters from Rajput et al [29][30][31] The methodology used to calculate permittivity change from individual salt species follows Self et al 32 Further details of the MD simulations can be found in the supplementary information document. Quantum chemistry calculations were undertaken with Gaussian 16 software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular dynamics (MD) simulations were carried out with the GROMACS software, 26 and initial configurations were prepared using Packmol. 27 Forcefield parameters for THF were taken from Spoel et al, 28 Ca 2+ parameters from the standard OPLS library, and BH4parameters from Rajput et al [29][30][31] The methodology used to calculate permittivity change from individual salt species follows Self et al 32 Further details of the MD simulations can be found in the supplementary information document. Quantum chemistry calculations were undertaken with Gaussian 16 software.…”
Section: Methodsmentioning
confidence: 99%
“…long-range electrostatics), may affect the various cluster equilibria differently, which we plan to investigate in upcoming work. To test whether the presence of dipolar clusters could facilitate formation of ionic species at high concentration through permittivity increases, as previously observed in other strongly associating electrolytes, 32,[40][41][44][45][46] we conducted simulations to determine the influence of several proposed clusters on the solution dielectric constant (supplementary information, Figure S6). The computed lowest free energy electrolyte structure, THF3Ca(BH4)2, possesses a bent geometry and a calculated dipole moment of 5 Debye.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…In experiments,t he dielectric constant at magnitude of million or billion Hz is used to represent the static dielectric constant of electrolytes and the dissociated ion pairs are no longer an unreasonable contribution to e. [17] Therefore,only contact ion pairs (CIPs) and solvents are considered when calculating the dielectric constant of electrolytes through formula S1. [18] On the other hand, cations will be solvated by solvents.P ositive charges carried by spherical cations can induce the centripetal orientation of solvent dipoles,f urther influencing the dielectric constant.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…66,67 Another example of binary salt systems for LIBs is Li + electrolytes with added CsPF 6 or CsTFSI, which have helped in passivation phenomena. [68][69][70] In low permittivity electrolytes, where polar associated salt species can help increase solution permittivity via polar contact-ion pairs, 3,5,9 the addition of a preferentially associated salt may be useful, as long as formation of larger but less polar aggregates (e.g. quadrupolar dimers) is minimized.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional wisdom holds that ion association is deleterious as it reduces the conductivity of LIB electrolytes. 1,2 However, newly emerging LIB electrolyte formulations, such as those described as low permittivity [3][4][5][6] or superconcentrated, 7,8 are promising alternative candidates. In these active research areas, associated salt plays unconventional roles.…”
mentioning
confidence: 99%